Bangladesh, selected issues in employment and development - Islam, Rizwanul; Muqtada, M.; Asian Regional Team for Employment Promotion (New Delhi : International Labour Organisation, Asian Employment Programme (ARTEP), 1986)
Selected papers of a seminar to discuss two reports, on economic development of Bangladesh, prepared by the Asian Regional Team for Employment Promotion.
Includes bibliographical references and index.
Keywords: Manpower policy -- Bangladesh -- Congresses; Labor supply -- Bangladesh -- Congresses; Bangladesh -- Economic conditions -- Congresses